PENGEMBANGAN PENDEKATAN PEMBELAJARAN BERBASIS MULTIPLE INTELLIGENCES BAGI MAHASISWA S1 PGMI IAIN SNJ CIREBON - Syamsi, Atikah (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2014)
To  support  efficacy  of  study,  basically  to  determine  approach  of  study  which in line with curriculum. Studying approach of study, a lot of type approach of  which  can  applied.  Among  others  approach  of  developed  study  from  an recognized  theory  with  theory  of  Multiple  Intelligence.  The  Theory  used  as  by approach  of  study,  because  it  talk  about  variety  which  related  to  educative participant  interest.  Basically  in  each  of  curriculum  is  focus  to  attainment  an certain  interest  to  educative  participant.  Approach  of  Multiple  Intelligence  even also look into that human being or someone have some intellegence potency. One of  the  intellegence  educative  by  participant  thats  which  must  be  developed,  so that in the end become an its very dominant interest.One of the matter which need to be paid attention in Multiple Intelligence is  the  existence  of  education  institutes  responsibility  to  be  succeeding  to  find  at least  one  ability  region  matching  with  its  intellegence  potency  and  this  matter have  positive  implication  to  make-up  of  its  life  or  which  is  ordinary  to  be recognized  with  term  of  make-up  of  life  skills.  Quality  of  Indonesia  human resource  these  days  is  reflection  of  education  system  which  in  this  time  go  into effect.This research represent Research and Development (having the character of research applied) that is research used to look for, to developing and testing an certain  finding  or  product.  This  Research  type  is  research  of  Experiment  with approach  of  mixture  that  is  qualitative  and  is  quantitative,  where  this  research aim  to  develop  new  approach  that  is  intelligences  multiple  to  student  of  PGMI IAIN  SNJ  Cirebon.  This  Matter  because  of  the  importance  of  education  which peculiarly  refer  at  student  skill  soft  as  behavioral  base  of  academic,  namely  for example mirror of education base on intelligences multiple which practically can improve  efficiency  of  someone  life  and  it  is  of  course  also  be  benefit  to  its environment.  By  having  efficiency  of  life  which  is  good  to  be,  expected  by  all college grad will be able to solve life problema faced.